PEMIKIRAN IMAM AL-GHAZALI DALAM KITAB AYYUHAL WALAD DALAM PENDIDIKAN KARAKTER ANAK - Hafiza, Hanifa; Qayyum, Aisyah Amatul (PREMIERE : Journal of Islamic Elementary Education, 2022)
Education has a function to develop abilities and shape the character and civilization of the nation with dignity in order to educate the lives of the nation's children. In relation to moral education, it appears that character education has the same orientation as moral education, namely character building. The purpose of writing conceptual articles is to add insight into: (1) how character education is in the ayyuhā al-walad book (2) how Imam Al-Ghazali's thoughts in early childhood character education. The Ayyuhal Walad book by Imam Al-Ghazali contains, among other things: about faith, namely faith in Allah SWT, advice to worship Allah, and educational advice for children. As for those related to education include: material about morals, methods and goals of education. Character education in the study of Imam Al-Ghazali's thoughts in the Ayyuhal Walad book includes two values, namely: individual values which include religious character and collective or social values which include social care, responsibility, hard work, appreciation for achievement.